2020
DOI: 10.1177/0363546520920561
|View full text |Cite
|
Sign up to set email alerts
|

Root Repair Versus Partial Meniscectomy for Medial Meniscus Posterior Root Tears: Comparison of Long-term Survivorship and Clinical Outcomes at Minimum 10-Year Follow-up

Abstract: Background: The importance of repair in medial meniscus posterior root tears (MMPRTs) has been increasingly recognized because it restores hoop tension. However, no study has compared the long-term outcomes between meniscectomy and repair. Hypothesis: Survivorship and clinical outcomes of repair would be better than those of meniscectomy after long-term follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: Between 2005 and 2009, patients with MMPRTs who had been followed up for at least 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 35 publications
3
61
0
Order By: Relevance
“…However, in our study, we did not evaluate the in uence of tear zones on the prevalence of repair as they were not recorded. Some authors believed that the posterior horn root tear should be repaired whenever possible, because detachment of posterior root can disrupt continuity of the circumferential bers and lead to loss of hoop tension [13,30]. We also observed that surgeons tend to repair meniscal posterior horn.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, in our study, we did not evaluate the in uence of tear zones on the prevalence of repair as they were not recorded. Some authors believed that the posterior horn root tear should be repaired whenever possible, because detachment of posterior root can disrupt continuity of the circumferential bers and lead to loss of hoop tension [13,30]. We also observed that surgeons tend to repair meniscal posterior horn.…”
Section: Discussionmentioning
confidence: 57%
“…The clinical outcomes between partial menisectomy and meniscal repair has been hotly debated in recent years. In a study performed by Kyu et al [13], they observed the difference of patients-reported outcomes among patients who have underwent meniscetomy or repair for at least 10 years follow-up and claimed that meniscal repair have a superior clinical outcomes. Stein et al [14] evaluated the rate of return to sports in athletes and found that patients underwent meniscal repair have a higher rate of return to sports (96.15%) comparing with those underwent partial menisectomy (50%) at 8.8-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In 20 studies, the knee was immobilized in a long cylinder leg cast/knee brace in full extension for the first 2 to 3 weeks. ‖ Immediate toe-touch weightbearing was allowed in 7 studies, 17,18,20,35,37,46,55 while immediate partial weightbearing was allowed in 2 studies. 19,39 Two studies allowed partial weightbearing at 2 weeks 27,28 ; 2 studies, at 4 weeks 24,48 ; and 6 studies, at 6 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] The study characteristics are presented in ►Table 1. These studies were published between 2011 and 2020, including seven retrospective comparative studies [25][26][27][30][31][32][33] and two prospective comparative studies. 28,29 Five studies included comparisons of root repair versus partial meniscectomy, 26,27,[29][30][31] while six included comparisons of root repair versus observation.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…These studies were published between 2011 and 2020, including seven retrospective comparative studies [25][26][27][30][31][32][33] and two prospective comparative studies. 28,29 Five studies included comparisons of root repair versus partial meniscectomy, 26,27,[29][30][31] while six included comparisons of root repair versus observation. 25,26,28,29,32,33 The sample size of the studies ranged from 38 to 90, with a total of 485 patients comprising 238 in the root repair group, 113 in the partial meniscectomy group, and 134 in the observation group.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%